Class A scavenger receptors regulate tolerance against apoptotic cells, and autoantibodies against these receptors are predictive of systemic lupus - Wermeling, Fredrik (The Rockefeller University Press, 2007)
Apoptotic cells are considered to be a major source for autoantigens in autoimmune diseases such as systemic lupus erythematosus (SLE). In agreement with this, defective clearance of apoptotic cells has been shown to increase disease susceptibility. Still, little is known about how apoptotic cell–derived self-antigens activate autoreactive B cells and where this takes place. In this study, we find that apoptotic cells are taken up by specific scavenger receptors expressed on macrophages in the splenic marginal zone and that mice deficient in these receptors have a lower threshold for autoantibody responses. Furthermore, antibodies against scavenger receptors are found before the onset of clinical symptoms in SLE-prone mice, and they are also found in diagnosed SLE patients. Our findings describe a novel mechanism where autoantibodies toward scavenger receptors can alter the response to apoptotic cells, affect tolerance, and thus promote disease progression. Because the autoantibodies can be detected before onset of disease in mice, they could have predictive value as early indicators of SLE.